2005
DOI: 10.1007/s11365-005-4774-7
|View full text |Cite
|
Sign up to set email alerts
|

The New Venture Decision: An Analysis Based on the GEM Project Database

Abstract: The new venture decision is a crucial stage in the process of creating a new business and is influenced by a series of social, demographic, cultural and economic factors, amongst others. These factors have been the subject of several studies, though there is still no widely accepted agreement on exactly how they affect the decision to create a new enterprise. This study will provide evidence on which variables affect the new venture decision, as well as the extent of their influence based on the analysis of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…As a result, it has been shown that the perception that an individual has about having the skills required for a new venture is relevant for making the decision to engage in a business start-up. The empirical study proves that someone who thinks they have the skills required to manage a new venture would be more likely to become an entrepreneur (Morales & Roig, 2005;De Clercq & Arenius, 2006;Davidsson & Honig, 2003;Autio & Wennberg, 2010).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…As a result, it has been shown that the perception that an individual has about having the skills required for a new venture is relevant for making the decision to engage in a business start-up. The empirical study proves that someone who thinks they have the skills required to manage a new venture would be more likely to become an entrepreneur (Morales & Roig, 2005;De Clercq & Arenius, 2006;Davidsson & Honig, 2003;Autio & Wennberg, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…It has been confirmed that knowledge of an employer has a positive relationship that is statistically significant to influence on the likelihood to engage in entrepreneurial activities (Klyver, Hindle & Meyer, 2008;Arenius & Kovalainen, 2006;Morales & Roig, 2005). Accordingly, social capital is considered an independent variable.…”
Section: Measures 321 Dependent and Independent Variablesmentioning
confidence: 89%
See 2 more Smart Citations
“…Recently models of intention that focus on attitudes have been proposed as a likely explanation for the entrepreneurial process. [34][35][36][37]. Those authors have viewed entrepreneurial decisions as a process; in this way Shapero expresses that "willingness to" act is another indispensable element in the process of the new venture decision, because, if the individual is not predisposed to this type of challenge, they will not be likely to act [36].…”
Section: Variables Allowing Public Education To Be Evaluated: the Rolmentioning
confidence: 99%